Light extraction from OLEDs for lighting applications through light scattering - Bathelt, Robert; Buchhauser, D.; Gärditz, C.; Paetzold, Ralph; Wellmann, Peter (Organic Electronics, 2007)
Theoretical considerations expect an increase of outcoupling efficiency of up to 70%. Experimental results yield an increase of outcoupling efficiency of about 22%. A software model based on raytracing to simulate light outcoupling from OLEDs through a scattering layer is introduced to gain a deeper understanding of the light extraction mechanism. We found that the scattering anisotropy factor g determined using the Henyey-Greenstein phase function and the effective absorbance of the OLED device have strong impact on outcoupling efficiency. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: OLED; Lighting; Outcoupling enhancement; Light scattering; Simulation; Raytracing